Ecological Causal Assessment - Norton, Susan B.; Cormier, Susan M.; Suter II, Glenn W. (Taylor & Francis, 2015)
Edited by experts at the leading edge of the development of causal assessment methods for more than two decades, Ecological Causal Assessment gives insight and expert guidance on how to identify cause-effect relationships in environmental systems. The book discusses the importance of asking the fundamental question "Why did this effect happen?" bef